Crystallographic studies on decameric Brucella spp. lumazine synthase: A novel quaternary arrangement evolved for a new function? - Klinke, Sebastian (2005)
The enzyme lumazine synthase (LS) catalyzes the penultimate step of riboflavin biosynthesis in plants, fungi and bacteria. The quaternary structure of the polypeptide differs between species, existing as pentamers or as icosahedrally arranged dodecamers of pentamers with 60 subunits. The pathogen Brucella spp. expresses two proteins that exhibit LS activity, RibH1 and RibH2. The latter enzyme belongs to a novel third category of quaternary arrangement for LS, that of a decameric structure assembled as a head-to-head oriented dimer of pentamers. In contrast, the RibH1 enzyme is assembled as a pentamer, as noted for several other LS enzymes. RibH1 appears to be the functional LS in Brucella spp., whereas RibH2, an enzyme of lower catalytic activity, is a virulence factor presumably acting in response to oxidative stress. The latter observation prompted us to further investigate the structural and catalytic properties of RibH2 in order to clarify the biological function of this enzyme. Here, we present a detailed analysis of two new crystallographic forms of RibH2 that explain the low catalytic activity of this enzyme in comparison with RibH1 and other LSs. Additionally, we analyze the effect of pH on the structure of this enzyme, and the binding of riboflavin and 6,7-dimethyl-8-ribityllumazine to its active site.